Design framework for optimized gridshell structures- and their potential applications - Persson, Rick (My University, 2023)
This master thesis investigates the design process of gridshell structures constructed from discretized elements, with a focus on optimizing the design through the exploration of key considerations regarding geometry, structure, and other potential challenges. The research results in a design handbook that provides valuable insight for architects and engineers, that would like to design a gridshell. Additionally, the thesis explores the potential of gridshell technology beyond typical applications with a concluding demonstration of the contents through the development of a bridge prototype that demonstrates the possibilities of gridshell technology. Purpose